Heavy metals concentration in surface water and sediment from tin mine effluents at Kepayang River, Perak, Malaysia - Ahmad Affandi, Farhana; Ishak, Mohd Yusoff (2017)
A preliminary study on physico-chemical properties and heavy metals concentrations (Al, As, Ba, Be, Cd, Co, Cu, Cr, Fe, Mn, Ni, Pb, Se, and Zn) was conducted at the nearest point of tin mine effluent in Kepayang River, Perak. Composite samples of water and sediment were analysed using ICP-MS and data were compared with the raw water of MOH and industrial soil of CCME guidelines. The concentration of Fe and As in both water and sediment were found to have exceeded the MOH and CCME guidelines. The output from this study will present the background report on metals concentration of tin mine effluent and be useful for future monitoring works.